COMPUTER VISION SYNDROME IN MEDICAL STUDENTS IN THE ERA OF THE COVID-19 PANDEMIC - Nydia Ongalia; Titiek Ernawati; Pauline Meryana (JOURNAL OF WIDYA MEDIKA JUNIOR, 2022)
Introduction: In the era of the COVID-19 pandemic, there are pretty drastic lifestyle changes, one of which is in the field of education. A distance learning system (PJJ) increased the use of Visual Digital Terminal (VDT) such as computers, laptops, mobile phones, and tablets for lecture and non-lecture activities. This causes a group of problems in the eyes and sight called Computer Vision Syndrome. Some factors that cause Computer Vision Syndrome include long duration, the distance between the eyes and screen is not optimal, incorrect ergonomics, angle of vision above eye level, and using the air conditioner. Aim: To analyze the factors that affect the incidence of Computer Vision Syndrome in students in the era of the COVID-19 pandemic. Methods: This research uses a cross-sectional study with non-probability sampling techniques through consecutive sampling. The research period is online from July 31st  to September 9th, 2021. Result: Respondents who experienced Computer Vision Syndrome were 92 people out of a total of 147 respondents. Multivariate analysis with multiple logistic regressions showed that total duration, distance, and room temperature significantly affected Computer Vision Syndrome (P<0.05), with the most dominant factor being the use of air conditioning (OR 6.214). Conclusion: Factors that significantly affect the incidence of Computer Vision Syndrome in FKUKWMS students in the era of the COVID-19 pandemic with distance learning system are total duration, distance, and air conditioner use.